Liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry screening procedure for urine samples in forensic casework compared to gas chromatography‐mass spectrometry. Issue 5 (3rd August 2016) - Fels, Helena; Dame, Torsten; Sachs, Hans; Musshoff, Frank
Abstract : This work represents the development, validation, and application of a liquid chromatography‐quadrupole‐time‐of‐flight mass spectrometry (LC‐QTOF‐MS) screening method for the detection of pharmaceutical substances and illicit drugs (acidic, basic, and neutral organic drugs) in urine samples. Time‐of‐flight mass spectrometry was performed using an LC‐Triple TOF 5600 system with electrospray ionization operated in both positive and negative mode, respectively. The limits of detection (LODs), determined for 34 substances, were < 10 ng/mL for 91% of the compounds. The limits of quantitation (LOQs) were < 20 ng/mL for 91% of the substances. The identification of the compounds was based on exact mass (< ± 5 ppm), retention time (<2%) if available, isotopic pattern fit (<10%) and library hit (>70%). These four parameters served as identification criteria and are discussed according to their role in identifying compounds even without reference substances. In routine casework, two in‐house XIC (extracted ion chromatogram) lists, consisting of 456 protonated and 26 deprotonated compounds were used and retention times for 365 compounds were available. Compared to the results found with the established gas chromatography‐mass spectrometry (GC‐MS) procedure, the findings with the LC‐QTOF‐MS screening method showed a good comparability. Results that were not detected by LC‐QTOF‐MS because of a missing entry in the targeted XIC list could retrospectively be confirmed by simply entering the elemental formula of the relevant substance into the software and reprocessing the sample. LC‐QTOF‐MS offers an attractive technique for the fast and specific identification of illicit drugs and toxic compounds in urine samples. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : This study describes the development, validation, and application of an LC‐QTOF‐MS screening method for the detection of pharmaceutical substances and illicit drugs (acidic, basic, and neutral organic drugs) in urine samples. The identification of the compounds was based on exact mass, retention time if available, isotopic pattern fit, and library hit. These four parameters served as identification criteria and are discussed according to their role in identifying compounds.